POWTOON ASSISTED GLASSER MODEL TO IMPROVE HIGH SCHOOL STUDENTS' WRITING SKILLS - Tambunan, Marlina Agkris; Manihuruk, Leonita Maria Efipanias (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study aims to improve the writing skills of SMA Negeri 1 Lintongnihuta students by using the glasser model with the help of local wisdom-based powtoon applications. This type of research is Classroom Action Research (PTK), in this case the teacher as the implementer of learning while the researcher as an observer. This research design uses the Kemmis and Mc model. Taggart. This research was carried out in the odd semester of the 2023/2024 academic year, namely in July. The subjects of this research were class X students at SMA Negeri 1 Lintongnihuta, consisting of 28 students. The object of research is students' writing skills. Data collection techniques use tests and observation. Data were analyzed descriptively and presented in table form. The results showed that there was an increase in students' writing skills, the average value of writing skills in the first cycle of the first meeting was 65.45 and the second meeting was 68.05. In cycle II the average writing skills score for the first meeting was 70.65 and the second meeting was 89.5. This means that improving learning outcomes by using the glasser model with the help of the local wisdom-based powtoon application can improve the writing skills of class X senior high school students.